PERSPEKTIF TAFSIR MAQASHIDI IBNU ASYUR TERHADAP KEPEMIMPINAN PEREMPUAN DALAM POLITIK - Dahrul Muftadin (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2022)
Women's leadership in the political realm in the Islamic community is often an issue and even a problem phenomenon that seems difficult to resolve. The existence of pros and cons related to the opinion of women's leadership in the political sphere also affects discussions and issues of public space for Muslims. It is not surprising then that many thinkers of Islamic studies have provided opinions or views related to women's leadership in the political realm, including in this case Ibn Asyur. Ibn Asyur has his own views related to women's leadership in the political realm. Ibn Asyur's thought was not born just like that but was born through the methodology and construction of thought from various aspects. This article discusses related to (1) how is the leadership of women in politics according to Ibn Asyur's thought? and (2) how is the analysis of Ibn Asyur's method in the thinking of women's leadership in the political sphere? The research objectives in this article are (1) to describe women's leadership in politics according to Ibn Asyur's thought; and (2) analyzing Ibn Asyur's method of thinking about women's leadership in the political realm. The conclusion of this research is that in the context of political leadership, women are placed according to their nature. Women may be involved in political matters has limitations. Considering that by nature, women cannot be equated with men, especially in physical terms.